Back Cover: Structural Changes during the Growth of Atomically Precise Metal Oxido Nanoclusters from Combined Pair Distribution Function and Small‐Angle X‐ray Scattering Analysis (Angew. Chem. Int. Ed. 37/2021). Issue 37 (28th June 2021) - Anker, Andy S.; Christiansen, Troels Lindahl; Weber, Marcus; Schmiele, Martin; Brok, Erik; Kjær, Emil T. S.; Juhás, Pavol; Thomas, Rico; Mehring, Michael; Jensen, Kirsten M. Ø.
Abstract : By combining X‐ray total scattering and small‐angle X‐ray scattering, it is possible to obtain unique insight into the formation of atomically precise nanoclusters. In a study of bismuth oxide clusters on page 20407, Michael Mehring, Kirsten M. Ø. Jensen et al. investigate the formation of [Bi38 O45 ] clusters from [Bi6 O8 ], and show that an intermediate structure of [Bi22 O26 ] plays an important role in the process. This intermediate structure was identified through a new automated modelling approach.